2020
DOI: 10.1002/hep4.1474
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Is an Agonistic Ligand for PPARα and Improves NASH by Activation of SIRT1/LKB1/pAMPK

Abstract: Nonalcoholic steatohepatitis (NASH) is recognized by hepatic lipid accumulation, inflammation, and fibrosis. No studies have evaluated the prolonged‐release pirfenidone (PR‐PFD) properties on NASH features. The aim of this study is to evaluate how PR‐PFD performs on metabolic functions, and provide insight on a mouse model of human NASH. Male C57BL/6J mice were fed with either normo diet or high‐fat/carbohydrate diet for 16 weeks and a subgroup also fed with PR‐PFD (300 mg/kg/day). An insulin tolerance test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 42 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…It suggested that PPAR α /SIRT1 signaling might be relative to the inflammation progression of NP. The results were consistent with the clues that PPAR α had a hand in inflammation by regulating SIRT1 [ 28 ]. Moreover, since SIRT1 was capable of bating inflammation by inhibition of NF- κ B [ 15 , 17 ], we also determined the levels of SIRT1 and acetylated NF- κ B p65 in CCI rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It suggested that PPAR α /SIRT1 signaling might be relative to the inflammation progression of NP. The results were consistent with the clues that PPAR α had a hand in inflammation by regulating SIRT1 [ 28 ]. Moreover, since SIRT1 was capable of bating inflammation by inhibition of NF- κ B [ 15 , 17 ], we also determined the levels of SIRT1 and acetylated NF- κ B p65 in CCI rats.…”
Section: Discussionsupporting
confidence: 90%
“…Ogawa et al found that the repression of microglial activation was associated with SIRT1-dependent PPAR α signaling [ 27 ]. Sandoval-Rodriguez et al showed that PPAR α improved nonalcoholic steatohepatitis via acting on SIRT1 [ 28 ]. However, whether the PPAR α /SIRT1 pathway was involved in NP development was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PFD has shown to be a powerful antifibrotic drug at dose of 300 mg/kg in an experimental HCC model induced by carbon tetrachloride in mice [66], but the pharmacodynamic mechanisms involved in responses generated by PFD have yet to be clarified. It has recently been shown that pirfenidone can bind to ligand binding domain of PPARα, which is a PPARc homolog, activating the SIRT1/LκB1/pAMPK indicating their ability to modify the epigenetic marks of the H3K9 [67]. Table 2 summarizes some important pharmacological characteristics of each one of the previously described therapies.…”
Section: Pirfenidone (Pfd)mentioning
confidence: 99%
“…MAFLD includes NASH, fibrosis, cirrhosis, and hepatocellular carcinoma [ 26 , 27 ]. Clinical and experimental data suggest that fatty liver can not only induce serious tissue damage and even cancer, but can also cause cardiovascular diseases [ 28 , 29 ].…”
Section: Nrf2 Connection With Liver Diseasesmentioning
confidence: 99%